Positive ALDH1A3 and Negative GPX3 Expressions Are Biomarkers for Poor Prognosis of Gallbladder Cancer. Issue 3 (25th August 2013) - Yang, Zhu-lin; Yang, Leping; Zou, Qiong; Yuan, Yuan; Li, Jinghe; Liang, Lufeng; Zeng, Guixiang; Chen, Senlin
Abstract : Background . Gallbladder cancers (GBCs) are highly aggressive cancers with high mortality. However, biological markers for the progression and prognosis of GBC are currently unavailable in the clinic. Objective . To identify biomarkers for predicting GBC metastasis and prognosis. Methods . We examined ALDH1A3 and GPX3 expressions in 46 squamous cell/adenosquamous carcinomas (SC/ASC) and 80 adenocarcinomas (AC) by using immunohistochemistry. Results . Positive ALDH1A3 and negative GPX3 expressions were significantly associated with lymph node metastasis and invasion of SC/ASCs and ACs. Univariate Kaplan-Meier analysis showed that either positive ALDH1A3( P < 0.001 ) or negative GPX3( P < 0.001 ) expression significantly correlated with decreased overall survival in both SC/ASC and AC patients. Multivariate Cox regression analysis showed that positive ALDH1A3 expression or negative GPX3 expression was an independent poor-prognostic predictor in both SC/ASC and AC patients. Conclusions . Our study suggested that positive ALDH1A3 and negative GPX3 expressions are closely associated with clinical pathological behaviors and poor prognosis of gallbladder cancer.